Extraordinary Activities on the Basis of the Spiritual Heritage of the Temurian Queens in the Improvement of Spiritual and Moral Values in Student Girls - Kurbonova Dilafruz Toshturdiyevna (International Journal on Integrated Education, 2022)
Student in the article girls from the audience of the heritage of the Temurid princesses except The lessons focus on upbringing, education, formation of spiritual and moral values, encouragement to read books. Spiritual and moral values teach girls the methods of education, discipline, good manners, manners, manners, and ways to purify the mind.